Repentance Inside Prison: The Perspective of a Woman in Tanjung Gusta Prison, Medan - Adek Trie Maylani; Sahdin Hasibuan; Endang Ekowati (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to explore the life experiences of female inmates at the Class IIA Tanjung Gusta Penitentiary in Medan, specifically in interpreting the process of repentance and religious rehabilitation during their incarceration. Utilizing a field study method, the findings indicate that religious guidance provided by religious teachers (ustadz), combined with vocational training, significantly contributes to the inmates' selftransformation. Furthermore, structured religious programs strengthen spiritual and emotional resilience, assisting inmates in managing remorse while fostering new hope. Additionally, independence training such as sewing, culinary arts, and handicrafts equips inmates with the productivity needed to reintegrate into society and achieve a prosperous life. Despite constraints in specialized women's health facilities, the gradual internalization of religious values and a professional work ethic reconstructs the inmates' identities into more responsible and positive individuals.